CLINICAL CHARACTERISTICS OF YOUNG ADULTS WITH HYPERTENSION REFERRED TO A SPECIALIST HYPERTENSION CLINIC. (April 2021) - Kennedy, Cormac; Farnan, Richard; Aftal, Zainab; Hall, Mary; Hemyrck, Linda; Stinson, John; O'Connor, Patricia; Hennessy, Martina; Barry, Michael
Abstract : Objective: Objective: Compared to older adults, young adults (18–39 years) with hypertension have poorer awareness of their conditions, are less likely to be treated and much less likely to have their blood pressure (BP) controlled as a result. The objective of this study was to identify the clinical characteristics of the young hypertensives, the extent of treatment and its success in achieving guideline BP targets. Design and method: Design: A pragmatic observational study of patients referred with hypertension to our clinic. Method: Consent for inclusion in the study was be requested from all patients attending the specialist hypertension clinic at St James Hospital from June to September 2019. Clinical details will be recorded to characterise the groups of interest. Details to be recorded from the patients first and most recent visit including demographics, referral information, co-morbidities, investigations and treatments. The study was approved by the local research ethics committee (Tallaght hospital, Dublin). T-tests and Chi-squared tests were applied as appropriate. Results: Results: 236 patients were recruited for the study of which 63 (26.7%) were young adults. The mean age of the young group was 32.1 years and the BMI was 30.3 kg/m2. 75% were either obese or overweight, both in line with the rest of the study cohort. 76% had a family history of hypertension. The young group were more likely to have controlled BP at a cut-off of 140/90mmHg (69.5 v 50.3%;p = 0.014) but this group were taking less anti-hypertensive medications compared to those forty years or older (1.41 drugs v 2.28;p < 0.001). While the young group were more likely to have controlled BP according to the new AHA guidelines (27.1% v 13.3%;p = 0.025; cut-off 130/80mmHg), the figures were similar for both groups when the ESH guidance was used due to a higher cut-off for those over 65 years (27.1 v 28.5%). Conclusions: Conclusions: This study suggests that younger patients with hypertension require less anti-hypertensive treatment to achieve BP control. It did not identify subgroups of patients within the young group, however, the group is notable for the extent of overweight and obese patients referred to the clinic.